Interplay between pi-bridges and positions of branched alkyl groups of unsymmetrical D-A-D-pi-A squaraines in dye-sensitized solar cells: mode of dye anchoring and the charge transfer process at the TiO2/Dye/electrolyte interface - Punitharasu, Vellimalai; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2017)
Far-red-absorbing squaraines possessing high molar absorptivity (>10(5) M-1 cm(-1)) are being attracted as high-efficiency chromophores in dye-sensitized solar cells (DSSCs). A series of donor acceptor -donor-pi spacer-acceptor (D-A-D-pi-A) unsymmetrical squaraines, PSQ1-5, with indoline donor and squaric/cyanoacetic acid acceptor units, were designed for sensitized solar cells. For extending the absorption toward the near-infrared region (NIR) and controlling the orientation on the TiO2 surface, benzene (PSQ1 and PSQ2) and thiophene (PSQ3-5) 7r-spacers and out-of-plane branched alkyl groups at the indoline that are away (PSQ1, PSQ3, and PSQS) or near (PSQ2 and PSQ4) the anchoring group, respectively, were introduced. Dynamic aggregation tendency of PSQ1 and PSQ3 than that of their isomers systematically modulates the orientation on the TiO2 surface, which in turn enhances photovoltaic performance. Absorptance on a thin transparent TiO2 film shows a visible-to-NIR response with an onset around 800 nm for PSQ3-5. Although there is resemblance in electrochemical redox levels, their high injection efficiency and recombination resistance differentiated impact on the way of anchoring and the dihedral angle between D-A-D units and g-spacers. DSSCs sensitized with PSQS achieved a PCE of 8.15% under simulated AM 1.5G illumination (100 mW cm(-2)), with the current density (j) and open-circuit voltage (Voc) of 19.73 mA cm(-2) and 630 mV, respectively. A clear comparison of the incident-photon-to-current conversion efficiency versus the light-harvesting efficiency correlates the structure-property relationship with J obtained for PSQ dyes. Electrochemical impedance spectroscopy was carried out to examine the TiO2/dye/electrolyte interface for further confirmation of the enhanced PCE of top-se-alkylated PSQS over that of other dyes.
Keywords: D-A-D-pi-A framework; dye-sensitized solar cell; H- and J-type aggregation; orientation of dyes; static/dynamic aggregates; unsymmetrical squaraine

Effect and position of spiro-bipropylenedioxythiophene pi-spacer in donor-pi-spacer-acceptor dyes for dye-sensitized solar cell - Sil, Manik Chandra; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (Dyes and Pigments, 2019)
Improper orientation and self-assembly of dyes on TiO2 surface are the main disadvantages at the dye-TiO2 interface that governs both charge injection and dye regeneration processes. In this report, a series of homo spiro-dimeric donor-pi-spacer-acceptor (D-pi-A) dyes based on bithiophene and terthiophene spacers with two-anchoring group containing dyes, TT1, T1T, TT1T were designed and synthesized by Pd-catalyzed successive Suzuki coupling followed by direct arylation reactions. The position of branching centre in TT1 and T1T was systematically varied, where the spiro unit was placed near and away from the anchoring carboxylic acid unit, respectively. The dimeric spiro-dye T1T showed device performance, which is 1.6 fold higher than its structural isomeric analogue TT1, of 3.9% with a V-oc and J(sc) of 0.593 V and 9.09 mA/cm2, respectively, whereas for the isomeric analogue TT1 a device performance of 2.45% (V-oc of 0.568 V and J(sc) of 6.25 mA/cm2) under simulated 1 Sun (100 mW/cm2) condition. The improved Voc for the dye T1T compared to TT1 dye was ascribed to the dipole moment exerted by the dyes on TiO2 surface. Further the PCE of 4.16% (V-oc 0.589 V, J(sc) 9.79 mA/cm2 respectively) maximum was observed, when an extra thiophene unit was inserted in between the donor and pi-spacer in dye TT1T. The shifting the position of branching spiroBiProDOT pi-spacer makes an impact on the device performance by synergistically enhancing both Voc and Jsc.
Keywords: CDCA; D-pi-A Spiro dye; Dye aggregation; dye-sensitized solar cell; spiroBiProDOT spacer